2013
DOI: 10.1038/bjc.2013.795
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers for detection of ovarian cancer and predicting cancer outcomes

Abstract: Background:Securing a diagnosis of ovarian cancer and establishing means to predict outcomes to therapeutics remain formidable clinical challenges. Early diagnosis is particularly important since survival rates are markedly improved if tumour is detected early.Methods:Comprehensive miRNA profiles were generated on presurgical plasma samples from 42 women with confirmed serous epithelial ovarian cancer, 36 women diagnosed with a benign neoplasm, and 23 comparably age-matched women with no known pelvic mass.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 37 publications
(50 reference statements)
1
105
0
1
Order By: Relevance
“…Deregulation or dysfunction of miRNAs contribute to cancer development (7)(8)(9)(10)(11)(12). A number of miRNAs have been identified as highly up-or downregulated in ovarian cancer (13)(14)(15)(16)(17)(18)(19). However, their roles in the pathogenesis of ovarian cancer remain unclear, and whether other miRNAs may be involved in the pathogenesis of ovarian cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation or dysfunction of miRNAs contribute to cancer development (7)(8)(9)(10)(11)(12). A number of miRNAs have been identified as highly up-or downregulated in ovarian cancer (13)(14)(15)(16)(17)(18)(19). However, their roles in the pathogenesis of ovarian cancer remain unclear, and whether other miRNAs may be involved in the pathogenesis of ovarian cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, Most of these studies have been performed on ovarian tissue samples. Recent studies have demonstrated that microRNAs are circulating freely in serum and other body fluids in a highly stable, cell-free form [22][23][24][25][26][27][28][29]. Circulating microRNAs are highly tissue specific that can identify origin of metastasis and can be used as non-invasive biomarkers for cancers [22,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…By investigating 42 OC patients, 36 women diagnosed with a benign neoplasm and 23 healthy controls, Shapira et al defined a 22-miRs profile to distinguish between OC and healthy controls and a 6-miRs profile to distinguish benign and OC patients (105).…”
Section: Circulating Mirsmentioning
confidence: 99%